2022
DOI: 10.1063/5.0071996
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how minority relativistic electron populations may dominate charge state balance and radiative cooling of a post-thermal quench tokamak plasma

Abstract: Minority relativistic electron populations can occur in a range of complex plasmas. Of specific interest is when runaway electrons form among the presence of high-atomic-number ion species in a tokamak plasma discharge. It has been recently demonstrated that ion charge state distributions and radiation losses at low bulk electron temperatures can be dominated by relativistic electrons, even though their density is orders of magnitude lower. This was attributed to the relativistic enhancement of electron impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Hansen and Shlyaptseva studied the effects of EEDF on collisional rates with two-temperature distribution [26]. Garland et al demonstrated that minority hot electron populations can dominate the charge states distributions and radiation losses by Ne and Ar impurities [27]. Recently, Dilmi and Boumali reported the effect of the types of EEDF and the ratio of hot electrons on the rate coefficients of Li [28].…”
Section: Introductionmentioning
confidence: 99%
“…Hansen and Shlyaptseva studied the effects of EEDF on collisional rates with two-temperature distribution [26]. Garland et al demonstrated that minority hot electron populations can dominate the charge states distributions and radiation losses by Ne and Ar impurities [27]. Recently, Dilmi and Boumali reported the effect of the types of EEDF and the ratio of hot electrons on the rate coefficients of Li [28].…”
Section: Introductionmentioning
confidence: 99%
“…For the Ohmic root, this leads to the familiar expression P η ≡ ηj 2 ∥ . For the RE root, this leads to an estimate of the net energy transferred to the plasma being given by P RE = E av j ∥ , though some of this energy will be lost via radiative losses in the channels of synchrotron radiation [18,19], bremsstrahlung [20], and line emission [21,22]. Thus, at steady state the heating of the bulk electrons will be bounded from above by P RE = E av j ∥ when on the RE root.…”
mentioning
confidence: 99%